Measurements of cloud condensation nuclei activity and droplet activation kinetics of fresh unprocessed regional dust samples and minerals - P. Kumar; I. N. Sokolik; A. Nenes (Atmospheric Chemistry and Physics, 2011)
This study reports laboratory measurements of cloud condensation nuclei (CCN) activity and droplet activation kinetics of aerosols dry generated from clays, calcite, quartz, and desert soil samples from Northern Africa, East Asia/China, and Northern America. Based on the observed dependence of critical supersaturation, sc, with particle dry diameter, Ddry, we found that FHH (Frenkel, Halsey and Hill) adsorption activation theory is a far more suitable framework for describing fresh dust CCN activity than Köhler theory. One set of FHH parameters (AFHH ∼ 2.25 ± 0.75, BFHH ∼ 1.20 ± 0.10) can adequately reproduce the measured CCN activity for all species considered, and also explains the large range of hygroscopicities reported in the literature. Based on a threshold droplet growth analysis, mineral dust aerosols were found to display retarded activation kinetics compared to ammonium sulfate. Comprehensive simulations of mineral dust activation and growth in the CCN instrument suggest that this retardation is equivalent to a reduction of the water vapor uptake coefficient (relative to that for calibration ammonium sulfate aerosol) by 30–80%. These results suggest that dust particles do not require deliquescent material to act as CCN in the atmosphere.